Interior Design Concept of University Library (Case Study: Vocational Education Program, University of Brawijaya - Debri Haryndia Putri; Tri Mega Asri (Program Pendidikan Vokasi Universitas Brawijaya, 2015)
College library has a role as the heart of the university. Library is the heart of the educational process. Ideally, a good college should be the one that has a good library to meet the needs of users. There are four psychological aspects that optimize arrangement of the room and support the library function as provider of services,namely: functional aspect, psychological aspect of the visitors, the aesthetic aspect and safety aspect of library materials. Descriptive and comparative methods were used in data collection. The comparative method was applied to make comparison between field and typology data, with the help of review of the literature as well. In this design, the typology stage was done by comparing Library National Technical Library, Cotbuss Library University, and Bond University Kearney Library. Comparing international design was done by considerating the vision and mission to be international university, the lack of vocational education program in university level, and the four aspects which refers to the user of the library that will ease the designer to think of a better solution to get best result for the design